2011
DOI: 10.1071/ah10890
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation and economic evaluation in Australia's healthcare system

Abstract: Evidence from health economic evaluations may provide valuable information in some decisions; however, at present, it is not central to many decisions. The study suggests that, for economic evaluation to be helpful in real-life policy decisions, it has to be placed into context - a context which is complex, political and often resistant to voluntary change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Decision makers have recommended that health economists should simplify language and analysis methods [14,20,25] and use standard formats for presenting economic evaluations [3,25,34]. Some decision makers favour the presentation of results in a disaggregated format (i.e.…”
Section: Accessibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Decision makers have recommended that health economists should simplify language and analysis methods [14,20,25] and use standard formats for presenting economic evaluations [3,25,34]. Some decision makers favour the presentation of results in a disaggregated format (i.e.…”
Section: Accessibilitymentioning
confidence: 99%
“…Approaches that have been suggested to improve the institutional acceptability of economic evaluations include making economic evaluations more relevant to the decision-making context [3,22], allowing flexibility in decision-making budgets to adopt recommended changes [2], incorporating budget and resource reallocation constraints in economic models [30,44], making economic evaluations more sensitive to questions to which healthcare decision makers need answers [3,22], involving all stakeholders in the economic evaluation process [22], and demonstrating direct benefit to the administrator or department [14]. Official requirements to demonstrate the cost effectiveness of interventions for third-party funding or reimbursement also promotes the development and use of economic evaluations [19].…”
Section: Institutional Acceptabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The review indicated that, at least with respect to medicines for paediatric patients, about which evidence can be especially difficult to generate for ethical reasons, the national and sub‐national approaches to evaluating health technologies are dissimilar. A complete picture of the dissimilarities is lacking, however, because research examining decision making in Australia at sub‐national levels is limited in volume and has overwhelmingly been conducted in the Australian state of New South Wales (NSW) . These studies have documented a complex situation in NSW, characterised by: limited resources available for HTA; inconsistent processes for the introduction, diffusion and prioritisation of technologies; and an overall paucity of evidence for assessment.…”
Section: Introductionmentioning
confidence: 99%